2013
DOI: 10.1016/j.jdent.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Do socioeconomic determinants affect the quality of posterior dental restorations? A multilevel approach

Abstract: Individual socioeconomic characteristics were associated with failure in posterior restorations in detriment of other clinical variables such as restorative material and type of tooth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 31 publications
0
48
0
6
Order By: Relevance
“…Although still under investigation on survival analysis of restorations, socioeconomic status of patients has been shown to affect the longevity of restorations, 30 probably motivated by the effect of socioeconomic determinants on dental caries. One of the few studies that investigated this association has shown, in a birth cohort study, that an unfavorable socioeconomic trajectory during life course is associated to a higher presence of subsequent unsatisfactory restorations.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Although still under investigation on survival analysis of restorations, socioeconomic status of patients has been shown to affect the longevity of restorations, 30 probably motivated by the effect of socioeconomic determinants on dental caries. One of the few studies that investigated this association has shown, in a birth cohort study, that an unfavorable socioeconomic trajectory during life course is associated to a higher presence of subsequent unsatisfactory restorations.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…One of the few studies that investigated this association has shown, in a birth cohort study, that an unfavorable socioeconomic trajectory during life course is associated to a higher presence of subsequent unsatisfactory restorations. 30 Authors concluded that people who had always lived in the poorest stratus of population had more restoration failures than those who lived in the richest layer. Similar results were observed for posterior restorations placed in a Dutch practice based research.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…Moreover, Correa et al 25 found that adolescents of 15 years of age with more than 5 decayed teeth had a higher risk of failed restorations. Our results may be explained by the increase in parental care in children with higher caries experience after the start of treatment.…”
mentioning
confidence: 99%
“…Diferentes fatores, como as características do paciente e do dente, o tamanho da cavidade, o operador e o material, influenciam na longevidade das restaurações (1,4) e as principais razões para as falhas são atribuídas a recidivas de cáries, fraturas do material restaurador e fatores relacionados ao paciente e sua característica socioeconômica (2,5).…”
Section: Introductionunclassified